Hydrocortisone-induced DNA endoreplication in human trabecular cells in vitro - Tripathi, Brenda J.; Tripathi, Ramesh C.; Swift, Hewson H. (Experimental eye research, 1989)
Primary monolayer cultures of trabecular cells and organ cultures of trabecular meshwork, obtained from normal eyes of human subjects (age range, 40 to 70 yr) were exposed to hydrocortisone at concentrations ranging from 10 −4 m to 10 −6 m for periods up to 4 weeks. Phasecontrast microscopy of cultured cells showed an increase in the size of the nuclei (up to three times) and in the extent of the cell cytoplasm compared to those in control cultures, and vesicular structures frequently accumulated in the cytoplasm. Microdensitometry of Feulgen-stained cell nuclei indicated that the cells of the trabecular meshwork in vivo have predominantly diploid levels (2C) of DNA. Many nuclei in the trabecular cell cultures were polyploid and contained DNA values of 4C, 8C, and 16C. Cultures which had been exposed to hydrocortisone showed a significant shift toward the higher DNA classes, in contrast to the untreated control cultures; the average increase in the amount of DNA per nucleus was 36%. We discuss the relevance of these findings to the disease glaucoma in man.